Study on Malpura sheep selected for resistance to Haemonchus contortus - SWARNKAR, SWARNKAR; SINGH, D; KUMAR, SUSHIL; MISHRA, A K; ARORA, A L (The Indian Journal of Animal Sciences, 2011)
This study describes response to natural infection with stronglye worms (predominantly Haemonchus contortus) in Malpura sheep selected for resistance and/or susceptibility to H. contortus. Progenies born during 2004–06 (spring) were evaluated for faecal egg count at naive and exposed stage of infection and 2 divergent lines were created by selecting progenies from sires with low mean FEC (R line) and from sires with high mean FEC (S line). The heritability estimate for FEC at naive and exposed stage of natural infection was 0.246±0.104 and 0.010±0.078, respectively. The performance of selected animals from both lines was compared over the years and no untoward effects on different performance traits were observed. The trends in intensity of infection from R line revealed reduced FEC and increased ability of sheep to withstand infection and maintain productivity even in the face of prolonged worm challenge even without drenching. Results revealed that resistance to H. contortus is moderately heritable, and selection for resistance is possible and will not adversely affect production parameters in semi-arid environment.